Literature Review on the Development of Cultural Tourism in the Tirta Empul Area, Tampaksiring - Made Arya Angelia Putri Darmastuti; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study is based on the growing trend of spiritual and cultural tourism in Bali, which, at sacred sites such as Tirta Empul Temple (Tampaksiring), not only opens up local economic opportunities but also raises management dilemmas that deserve careful attention particularly regarding the tendency to commodify rituals and environmental pressures that have implications for water quality and the cleanliness of the area. This research aims to map the development of cultural tourism in Tirta Empul while critically synthesizing the main attractions, various impacts, and management strategies most frequently reported in the literature. Theoretically, the discussion links Tri Hita Karana, Community-Based Tourism, and heritage management perspectives authenticity to understand how sacred and tourist functions are negotiated in practice. The method used is a Narrative Literature Review of publications from 2015–2025 searched through Google Scholar, SINTA, and university repositories; studies were selected through title-abstract relevance screening and then analyzed thematically. Interestingly, the findings indicate that melukat (temple) and heritage values ​​are the primary drivers of visitation, but issues of desacralization, overcrowding, and recurring waste/garbage remain unresolved challenges. Therefore, the synthesis recommends strengthening sacred space zoning, implementing a code of ethics supported by cultural interpretation, managing visitor flow, and strengthening the role of traditional villages, while emphasizing the importance of regularly measuring visitor carrying capacity. Keywords: Cultural Tourism, Spiritual Tourism, Tirta Empul.